CUSTOMER LOYALTY DITINJAU DARI ADVERTISING, SALES PROMOTION DAN BRAND IMAGE PADA FRANCHISE ICE CREAM & TEA - Atiya Fadila; Lista Meria (JURNAL LENTERA BISNIS, 2024)
Customer loyalty becomes an important factor and a valuable asset for a business when customers have a positive attitude towards the product, thus motivating them to make repeat purchases. This research aims to analyze the influence of advertising, sales promotion, brand image on customer loyalty. The population of this research is made up of Mixue, Wedrink, and Momoyo customers. This research used a purposive sampling method to take samples from a total of 126 respondents. The data was analyzed statistically by applying PLS-SEM to test the proposed hypothesis. The results of this research show that sales promotion has a positive effect on customer loyalty, advertising has a positive effect on brand image, and sales promotion has a positive effect on brand image. Meanwhile, brand image has no positive effect on customer loyalty and advertising has no positive effect on customer loyalty. The managerial implication of this research is that companies need to strengthen sales promotion through various promotions and attractive offers so that they can motivate customers to buy products continuously and be loyal to the brand. In future research, it is recommended to add the age range, expand the respondent area and carry out in-depth analysis by looking at other factors such as product quality, price, location, and customer satisfaction which can influence customer loyalty, so that in future research we can obtain more comprehensive and detailed data. Keywords: Advertising; Sales Promotion; Brand Image; Customer Loyalty